Personality Factors' Impact on the Structural Integrity of Mentalizing Network in Old Age: A Combined PET-MRI Study - Giannakopoulos, Panteleimon; Rodriguez, Cristelle; Montandon, Marie-Louise; Garibotto, Valentina; Haller, Sven; Herrmann, François R. (Frontiers in Psychiatry, 2020)
The mentalizing network (MN) treats social interactions based on our understanding of other people's intentions and includes the medial prefrontal cortex (mPFC), temporoparietal junction (TPJ), posterior cingulate cortex (PCC), precuneus (PC) and amygdala. Not all elders are equally affected by the aging-related decrease of mentalizing abilities. Personality has recently emerged as a strong determinant of functional connectivity in MN areas. However, its impact on volumetric changes across the mentalizing network in brain aging is still unknown. To address this issue, we performed a longitudinal investigation combining MRI data and PET amyloid in a community-based series of 65 cognitively preserved, APOE genotyped elderly individuals followed-up longitudinally for a mean duration of 54 months. Personality was assessed with the Neuroticism Extraversion Openness Personality Inventory-Revised. Regression models corrected for multiple comparisons were used to identify predictors of volume loss including time, age, sex, personality, amyloid load, presence of APOE epsilon 4 allele and cognitive evolution. In mixed regression univariate models, lower Agreeableness scores were associated with better volume preservation in posterior cingulate cortex (PCC), precuneus (PC) and amygdala bilaterally. This was also the case for the association between lower Agreeableness as well as lower Conscientiousness and right medial prefrontal cortex (mPFC) volume loss. In multiple linear regression models, the associations regarding Agreeableness persisted in left PC and right amygdala. This was also the case for the association between Conscientiousness and right mPFC volume loss (26.3% of variability, significant age, sex). Both Agreeableness (Modesty) and Conscientiousness (order, dutifulness, achievement striving and self-discipline) were positively related to increased volume loss in cortical components of the MN. In conclusion, this combined PET amyloid-MRI study challenges the beneficial role of higher levels of Agreeableness and Conscientiousness in old age showing that they are associated with an increased rate of volume loss within the mentalizing network.